Gender Difference in Chronic Cough: Are Women More Likely to Cough? - Bai, Haodong; Sha, Bingxian; Xu, Xianghuai; Yu, Li (Frontiers in Physiology, 2021)
Chronic cough is a common complaint for patients to seek medical cares all over the world. Worldwide, about two thirds of chronic cough patients are females. However, in some regions of China the prevalence of chronic cough between sexes is roughly the same. Estrogen and progesterone can not only have an effect on transient receptor potential vanilloid 1 channel, eosinophils and mast cells, but also influence laryngeal dysfunction, gastroesophageal reflux disease and obstructive sleep apnea hypopnea syndrome, which may lead to increased cough sensitivity in women. On the other hand, the quality of life was adversely affected more in female patients with chronic cough. Both hormones possibly cause gender difference in chronic cough.